2013
DOI: 10.5665/sleep.2292
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sleep Disordered Breathing Reverses Low Fetal Activity Levels in Preeclampsia

Abstract: The effectiveness of continuous positive airway pressure in improving fetal movements suggests a pathogenetic role for sleep disordered breathing in the reduced fetal activity and possibly in the poorer fetal outcomes associated with preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 22 publications
2
90
0
5
Order By: Relevance
“…1 SDB, independent of maternal BMI, is associated with an increased risk of hypertension in pregnancy, as well as maternal morbidity. 73,78,[80][81][82][83][84][85][86] In one study, preeclampsia, a hypertensive syndrome in pregnancy, was significantly more common among snorers than non-snorers (10% versus 4%, p < 0.05), as was gestational hypertension (14% versus 6%, p < 0.01). 87 This was recently corroborated in a report by O'Brien and colleagues, who found that pregnancy-onset snoring was independently associated with gestational hypertension (OR 2.36 [1.48-3.77], p < 0.001) and preeclampsia (OR 1.59 [1.06-2.37], p = 0.024) in 1,719 third-trimester pregnant women.…”
Section: Sleep Related Breathing Disorders In Pregnancymentioning
confidence: 99%
“…1 SDB, independent of maternal BMI, is associated with an increased risk of hypertension in pregnancy, as well as maternal morbidity. 73,78,[80][81][82][83][84][85][86] In one study, preeclampsia, a hypertensive syndrome in pregnancy, was significantly more common among snorers than non-snorers (10% versus 4%, p < 0.05), as was gestational hypertension (14% versus 6%, p < 0.01). 87 This was recently corroborated in a report by O'Brien and colleagues, who found that pregnancy-onset snoring was independently associated with gestational hypertension (OR 2.36 [1.48-3.77], p < 0.001) and preeclampsia (OR 1.59 [1.06-2.37], p = 0.024) in 1,719 third-trimester pregnant women.…”
Section: Sleep Related Breathing Disorders In Pregnancymentioning
confidence: 99%
“…45 In a different study, nasal CPAP was shown to increase fetal movements in patients studied with polysomnography and continuous ultrasound. 28 These studies have been the subject of an insightful analysis by O’Brien et al 121 …”
Section: Is There a Role For Cpap In Preeclampsia?mentioning
confidence: 99%
“…Recent evidence supporting this concept indicated that even treating very mild SDB (e.g. snoring or flow limitation) with nasal continuous positive airway pressure (CPAP) improves haemodynamic parameters and fetal wellbeing [32][33][34][35][36]. Figure 1 provides guidance for our proposed model explaining potential pathways linking sleep disturbances and pregnancy complications.…”
Section: Potential Pathophysiologic Mechanisms For Adverse Pregnancy mentioning
confidence: 99%